2017
DOI: 10.1016/j.ijpharm.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanovehicles with adjustable surface properties for overcoming multiple barriers simultaneously in oral administration

Abstract: Lipid nanoparticles (LNs) are widely investigated for oral drug delivery, and for achieving significant advantages in colloidal stability, biocompatibility and scaled-up possibility. However, researchers face challenge of developing methods to improve the ability of LNs in overcoming multiple barriers (i.e., mucus and epithelium barrier) in gastrointestinal (GI) tract because of the contradictory requirement of nanoparticle (NP) surface properties in the two processes. Therefore, we designed novel LNs with adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Hydrophobic interaction between NPs and hydrophobic groups on mucin could induce unwanted entrapment in mucus. Previous studies have demonstrated the importance of hydrophilic/hydrophobic balance in simultaneously penetrating the mucus layer and entering the epithelium. , Consequently, taking the basal exocytosis into consideration, we may need to find a “triple balance” upon surface hydrophobicity for the maximum mucus-penetration, endocytosis, and transcytosis. Apart from hydrophobicity, some other surface properties may also affect NP exocytosis.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic interaction between NPs and hydrophobic groups on mucin could induce unwanted entrapment in mucus. Previous studies have demonstrated the importance of hydrophilic/hydrophobic balance in simultaneously penetrating the mucus layer and entering the epithelium. , Consequently, taking the basal exocytosis into consideration, we may need to find a “triple balance” upon surface hydrophobicity for the maximum mucus-penetration, endocytosis, and transcytosis. Apart from hydrophobicity, some other surface properties may also affect NP exocytosis.…”
Section: Results and Discussionmentioning
confidence: 99%
“…16 For dye release evaluation, PBS (pH 5.0 or 7.4) were selected as release medium. In brief, 1 mL of NP suspension was sealed in a dialysis bag (MWCO: 100 kDa) and released against 40 mL of release medium for 24 h. 17 At determined time points, an aliquot of exterior medium (50 μL) was withdrawn and measured via Varioskan Flash Multimode Reader. The accumulative amount of released dye was then calculated.…”
Section: Stability Studymentioning
confidence: 99%
“…How the functional groups on the surface affected the hydrophilicity of MSNs was also further investigated. Since viruses possess a hydrophilic surface, the more hydrophilic the surface of MSNs, the better mimicking the virus, to enhance the oral absorption of MSNs . According to the report, the prepared nanoparticle suspensions with different concentrations were mixed with an equal volume of CBB (0.1 mM).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…To investigate the mechanism of cellular internalization of OA-CAT3-SLN, various specific endocytic inhibitors were evaluated in the uptake study. Chlorpromazine (10 µg/mL) was used as the clathrin-mediated endocytic inhibitor, nystatin (5 µg/mL) as the caveolae structure and function abolisher, and methyl-β-Cyclodextrin (MCYP, 13 mg/mL) as the disruptor of lipid rafts [35][36][37]. The inhibitors were added to the cell monolayer and pre-treated for 30 min before the test.…”
Section: In Vitro and In Vivo Bio Evaluation Of Oa-cat3-sln Transepitmentioning
confidence: 99%